PENGARUH INFLASI, UPAH MNIMUM REGIONAL DAN KESEMPATAN KERJA PADA SEKTOR INDUSTRI MANUFAKTUR TERHADAP PENGANGGURAN TERDIDIK DI PROVINSI BANTEN - sugeng setyadi; Rindang Tri putri (FEB Universitas Sultan Ageng Tirtayasa, 2017)
One of the macro-economic problem that often occurs is the problem of umemployment. In Banten Province where unemployment rates are educated each year to experience fluctuating conditions. This is caused by several factors including inflation, minimum wage and employment, where employment opportunities are more dominant in the manufacturing sector.This study was conductedtoexamine the effect ofinflation, Minimum Wage(UMR), Employment Opportunitieson the Number ofUnemployedEducated(Y) in the province ofBanten. The data usedaresecondary datain the form ofpanel datacombinedwithperiodic data(time series) andtenyears ofrandom data(cross section) threecountiesandcities. Testanalysis ismultiple regression analysisusingpanel datawithpartialstatistical test(t test) with a95percentconfidencelevel(α =0,05). F testperformedandmeasured byR2test(test determinants).The conclusion thatcan bedrawnin this paper isthatinflationwillnot affect thedecrease in the numberof educatedunemployed, the rate of change inthe minimum wageaffectthe changeof educatedunemploymentand decreaseaffecting theemploymentopportunitiesof educatedunemployment.